2015
DOI: 10.1177/0265532215579530
|View full text |Cite
|
Sign up to set email alerts
|

How do utterance measures predict raters’ perceptions of fluency in French as a second language?

Abstract: While the research literature on second language (L2) fluency is replete with descriptions of fluency and its influence with regard to English as an additional language, little is known about what fluency features influence judgments of fluency in L2 French. This study reports the results of an investigation that analyzed the relationship between utterance fluency measures and raters' perceptions of L2 fluency in French using mixed-effects modeling. Participants were 40 adult learners of French at varying leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 37 publications
3
51
0
Order By: Relevance
“…The results of the current study appear to suggest that speech rate and mean length of run might be better categorized as composite measures rather than part of the speed fluency dimension. Further evidence for the composite nature of these two measures can be seen if the relationship among the measures of fluency, as indicated by correlations, is considered, as has been done in previous research (Bosker et al., ; Préfontaine et al., ). In the current data, a correlation analysis using fluency measurements from the pre‐sojourn data collection point (see Appendix ) indicated that speech rate correlated with most other measures of fluency, except average silent pause between ASU and measures of repair.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The results of the current study appear to suggest that speech rate and mean length of run might be better categorized as composite measures rather than part of the speed fluency dimension. Further evidence for the composite nature of these two measures can be seen if the relationship among the measures of fluency, as indicated by correlations, is considered, as has been done in previous research (Bosker et al., ; Préfontaine et al., ). In the current data, a correlation analysis using fluency measurements from the pre‐sojourn data collection point (see Appendix ) indicated that speech rate correlated with most other measures of fluency, except average silent pause between ASU and measures of repair.…”
Section: Discussionmentioning
confidence: 87%
“…One way of choosing measurements is to opt for those that correspond to listeners' perceptions of fluent speech. Research comparing perceived fluency to utterance fluency (see e.g., Cucchiarini, Strik, & Boves, 2000, 2002Kormos & Dénes, 2004;Préfontaine, Kormos, & Johnson, 2016;Rossiter, 2009) has shown, for example, that measurements such as speech rate and mean length of run correlate to and explain variance of raters' judgements; however, the findings from this line of research are not consistent, and factors such as task type (read vs. spontaneous speech) and linguistic accuracy have been found to influence results. It is also important to consider, as noted in De , that perceived fluency ratings are dependent on the definitions and instructions given to raters or the notions that noninstructed raters have about fluency.…”
Section: Defining and Measuring Fluencymentioning
confidence: 96%
“…A language proficiency assessment research, for example, conducted by Carroll and Bailey (2016) shows that there are different variables such as EFL student and non-EFL students, and tests in four sub-domains: speaking, writing, reading, and listening. It is also noticed in another study of second language fluency by Préfontaine, Kormos and Johnson (2016) that various variables were used such as class variables: beginning, intermediate and advanced; native speaker variables: British, American, and Canadian.…”
Section: Advantagesmentioning
confidence: 99%
“…L2 perceived fluency refers to subjective judgments of L2 speakers' oral fluency. Researchers often use such judgments to assign fluency levels to the L2 speakers under study (Bosker et al 2012;Derwing et al 2004;Préfontaine et al 2015). Perceived fluency can reflect something about the objective characteristics of oral fluency.…”
Section: L2 Perceived Fluencymentioning
confidence: 99%